Portofolio demi Sertifikasi Guru, Harapan atau Impian - Subijanto M.Ed (Jurnal Pendidikan dan Kebudayaan, 2010)
A professional teacher is a yearned-for personnel in terms of creating qualified human resource for the Indonesian development. The government accomplished he yearning by the program of teacher certification that is aimed at specifying teacher appropriateness to become a teaching agent, increasing the quality of education success and teachers status, promote teachers professionalism and prosperity. In order to get a certificate the teacher has to possess academic qualification at least of bachelor or fourth diploma degree and has competency to realize the national education goal. In order to get the certificate the teacher has to pass the certification test as shown by various documents in the set of portfolio. Many people are skeptical towards the certification accomplishment because of the practices of corruption activities for the purpose of obtaining a piece of magical certificate that should be used to get the increase of teacher quality and income. This article is to spotlight numerous difficulties and barriers faced by the teachers in fulfilling the demands of portfolio so that the teacher certificate could become an aspiration that would be accomplished or on the contrary it would be nothing other than a dream because of the impossibility to fulfill the certification demands.